PENGARUH KEPERCAYAAN, KEMUDAHAN, RELIGIUSITAS DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN SPAYLATER - Wulan Dary, Riszha; Pudjihardjo, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The development of globalization has an impact on human life by bringing changes to human life. various fields today. One of them is the field of technology and information that is developing and cannot be separated from the internet. Many marketplaces have sprung up in Indonesia, this research focuses on the shopee marketplace. Shopee is the most visited marketplace in Indonesia. Shopee provides various payment methods, one of which is Spaylater. The Spaylater system is the same as a credit card in that it provides loans to its users. The younger generation, namely Generation Z, currently dominates internet users in Indonesia. They mostly use it for social media or online shopping. The purpose of this study was to determine the effect of trust, convenience, religiosity and risk perception on purchasing decisions using Spaylater. This study uses a descriptive quantitative approach with multiple linear regression analysis. The sampling method used is non-probability sampling with purposive sampling technique. The sample of the population is 125 respondents from generation Z Muslims in Indonesia. The results obtained that trust, ease of use, religiosity and perceived risk together have a significant effect on purchasing decisions using Spaylater.